1999
DOI: 10.3201/eid0506.990608
|View full text |Cite
|
Sign up to set email alerts
|

Hantavirus Reservoir Hosts Associated with Peridomestic Habitats in Argentina

Abstract: Five species of sigmodontine rodents have been identified in Argentina as the putative reservoirs of six circulating hantavirus genotypes. Two species of Oligoryzomys are associated with the genotypes causing hantavirus pulmonary syndrome, Oligoryzomys flavescens for Lechiguanas and O. longicaudatus for Andes and Oran genotypes. Reports of human cases of hantavirus pulmonary syndrome prompted rodent trapping (2,299 rodents of 32 species during 27,780 trap nights) at potential exposure sites in three disease-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
54
1
6

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 4 publications
9
54
1
6
Order By: Relevance
“…The identification of the Pergamino virus in A. azarae also agrees with previous studies (Calderón et al 1999, Padula et al 2000a). The detection of Pergamino virus in one individual of O. flavescens suggests that the virus was transmitted between A. azarae and O. flavescens, but it could had been an incidental infection which not resulted in persistent infection.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The identification of the Pergamino virus in A. azarae also agrees with previous studies (Calderón et al 1999, Padula et al 2000a). The detection of Pergamino virus in one individual of O. flavescens suggests that the virus was transmitted between A. azarae and O. flavescens, but it could had been an incidental infection which not resulted in persistent infection.…”
Section: Discussionsupporting
confidence: 81%
“…The rates of hantavirus seroprevalence found in A. azarae and O. flavescens in this study were almost three times higher than those recorded by Calderón et al (1999) in localities of Buenos Aires province where cases of HPS have been reported: 9.3, n = 291 versus 2.7%, n = 549 P < 0.0001 for A. azarae and 13.5, n = 37 versus 4.7%, n = 170 P < 0.05 for O. flavescens, for this study and Calderón's study, respectively, test of comparison of two percentages (Bailey 1981). Strong variations in seroprevalences are not only evident when comparing studies conducted by different authors, but also within habitats and times (Abbott et al 1999.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…The host-virus relationships related to HFRS are Apodemus agrarius-Hantaan virus (HTNV) (32), Rattus norvegicus-Seoul virus (SEOV) (10), Apodemus flavicollisDobrava virus (DOBV) (4), and Myodes glareolusPuumala virus (PUUV) (44,60). The host-virus relationships in HPS are Peromyscus maniculatus-Sin Nombre virus (SNV) (43), Peromyscus leucopus-New York virus (NYV) (53), Sigmondon hispidus-Black Creek Canal virus (BCCV) (50,51), Oryzomys palustris-Bayou virus (BAYV) (29,55), Oligoryzomys longicaudatus-ANDV (8), Oligoryzomys flavescensLechiguanas virus (LECV) (8), Oligoryzomys microtisRio Mamore virus (RMV) (6), and Calomys lauchaLaguna Negra virus (LNV) (21).…”
mentioning
confidence: 99%